CORPUS LINGUISTICS RESEARCH: ANALYZE THE USE OF LINKING VERB IN CNN ARTICLES - Farhan Firdaus (Faculty of Education and Teachers Training, 2021)
In this article, the researcher will discuss linking verbs. Linking verbs are verb that fills in as an association between a subject and additional data about that subject. This article will discuss the use of linking verbs in some news articles on CNN.com. This research was carried out to fulfill the Corpus Linguistic task given to us as English Department Tidar University students. I choose CNN.com because CNN.com is one of the largest mass media in the world. Mass media that was first initiated by Ted Turner and Reese Schonfeld and first launched in 1980 and is a subsidiary of WarnerMedia is also the first TV channel that broadcasts news 24 hours non-stop. Researchers use qualitative descriptive method to knows how often the linking verb is used in CNN.com news article. The result shows that CNN.com use linking verb like “is” (300), “are” (212), “be” (173), “was” (169), “have” (142), “were” (65), “will be” (33), “get” (25), “has been” (24), “come” (14), “keep” (13), “could be” (13), “does” (9), “remain” (8), “felt” (8), “act” (7), “had been” (7), “became” (5), “has become” (5) in more than 30 news article in there.Keywords: linking verb, CNN.com, news article